Pembelajaran Teorema Pythagoras dengan Metode Discovery melalui Media Papan Tegras - Hapizoh, Hapizoh (Jurnal Didaktika Pendidikan Dasar, 2019)
The purpose of this study is to improve the understanding of the concept of the Pythagorean Theorem by applying discovery methods through the media on the board of students in Grade VIII.2 State Junior High School 26 Palembang. This research is a classroom action research by implementing the discovery method through the integrity board in the learning process of the Pythagorean Theorem. Data collection techniques were carried out by tests, interviews, observation sheets, and field notes. The results of this study indicate that the discovery method through integrity board has the advantage of overcoming students' misunderstanding in the material of the Pythagorean Theorem so that this impacts on student learning outcomes. The results of this final test further strengthen the interview subject's statement that students' understanding of the material is increasing. The final test score average of Cycle 1 is 61.43, Cycle 2 is 70.14 with a success rate of 57.14% to 77.14%, and Cycle 3 to 76.29 with a success rate of 77.14% to 88.57%.